2017
DOI: 10.1002/nbm.3803
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous imaging of hyperpolarized [1,4‐13C2]fumarate, [1‐13C]pyruvate and 18F–FDG in a rat model of necrosis in a clinical PET/MR scanner

Abstract: A co-polarization scheme for [1,4- C ]fumarate and [1- C]pyruvate is presented to simultaneously assess necrosis and metabolism in rats with hyperpolarized C magnetic resonance (MR). The co-polarization was performed in a SPINlab polarizer. In addition, the feasibility of simultaneous positron emission tomography (PET) and MR of small animals with a clinical PET/MR scanner is demonstrated. The hyperpolarized metabolic MR and PET was demonstrated in a rat model of necrosis. The polarization and T of the co-pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…5a) in breast cancer 106 and efficient co-polarization schemes offer simultaneous probing of multiple metabolic pathways. 107 Hyperpolarization of the reduced and oxidized forms of vitamin C-namely [1-13 C]dehydroascorbate and [1-13 C] ascorbate, respectively-offers a novel means to probe intracellular redox status, a critical factor in normal and abnormal cellular function. 108,109 High concentrations of [1-13 C]ascorbate can be observed post-injection of [1-13 C]dehydroascorbate, and reduced HP [1-13 C]ascorbate signal has been utilized as an MR biomarker of renal oxidative stress.…”
Section: D-dnp Beyond [1-13 C]pyruvate: Other Candidate Molecular Probesmentioning
confidence: 99%
“…5a) in breast cancer 106 and efficient co-polarization schemes offer simultaneous probing of multiple metabolic pathways. 107 Hyperpolarization of the reduced and oxidized forms of vitamin C-namely [1-13 C]dehydroascorbate and [1-13 C] ascorbate, respectively-offers a novel means to probe intracellular redox status, a critical factor in normal and abnormal cellular function. 108,109 High concentrations of [1-13 C]ascorbate can be observed post-injection of [1-13 C]dehydroascorbate, and reduced HP [1-13 C]ascorbate signal has been utilized as an MR biomarker of renal oxidative stress.…”
Section: D-dnp Beyond [1-13 C]pyruvate: Other Candidate Molecular Probesmentioning
confidence: 99%
“…The [2‐ 13 C]Pyr (14 M) sample is prepared by mixing AH111501 trityl radical (GE Healthcare, Oslo, Norway) in [2‐ 13 C]Pyruvic acid (Sigma Aldrich, St Louis, MO), whereas the [1,4‐ 13 C 2 ]Fum (3.5 M) sample was prepared by dissolving [1,4‐ 13 C 2 ]Fumaric acid (Cambridge Isotope Laboratories, Cambridge, MA) crystals in dimethyl sulfoxide (DMSO) (Sigma Aldrich, USA) followed by the addition of AH111501 trityl radical. The copolarized mixture consists of 50 µL of [2‐ 13 C]Pyr and 100 µL of [1,4‐ 13 C 2 ]Fum and the copolarization was done using a SPINlab Hyperpolarizer (Research Circle Technology) operating at 5.0T and 0.82 K. Following the procedure described by Eldirdiri et al, the sample mixture was prepared by first adding the measured [2‐ 13 C]Pyr to the sample vial and freezing it.…”
Section: Methodsmentioning
confidence: 99%
“…The RF pulses and transmitter frequency are shifted alternately during each subsequent sampling interval to acquire both sub-bands during same experiment. ]Fum and the copolarization was done using a SPINlab Hyperpolarizer (Research Circle Technology) operating at 5.0T and 0.82 K. Following the procedure described by Eldirdiri et al, 19 the sample mixture was prepared by first adding the measured [2-13 C]Pyr to the sample vial and freezing it.…”
Section: Rf Pulse Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies showed that it could be used to provide early evidence of tumor cell death after treatment (Gallagher et al, 2009;Witney et al, 2010) and that it was more effective at detecting low levels of diffuse necrosis than diffusion-weighted 1 H MRI (Bohndiek et al, 2010). The technique can also be used to detect cell death in other tissues, such as kidney (Clatworthy et al, 2012) and muscle (Eldirdiri et al, 2017). In a recent study, hyperpolarized [1-13 C]pyruvate, [ 13 C]urea and [1,4-13 C 2 ]fumarate were used to assess the effects of transcatheter arterial embolization in an orthotopic rat hepatocellular carcinoma model.…”
Section: Magnetic Resonancementioning
confidence: 99%